2016
DOI: 10.1016/j.jinteco.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A global view of productivity growth in China

Abstract: How does a country's productivity growth a¤ect worldwide real incomes through international trade? In this paper, we take this classic question to the data by measuring the spillover e¤ects of China's productivity growth. Our framework features traditional terms-of-trade e¤ects and new trade home market e¤ects as suggested by the theoretical literature and works from a reference point which perfectly matches industry-level trade.Focusing on the years 1995 to 2007, we …nd that the cumulative welfare e¤ect on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 31 publications
1
90
0
Order By: Relevance
“…Arkolakis et al (2012) briefly discuss a multi-industry formula in an extension but never contrast it to their aggregate formula or use it to actually calculate the gains from trade. Caliendo and Parro (2015), Hsieh and Ossa (2012), Ossa (2014), and others work with multi-industry versions of standard trade models but also do not point out that cross-industry heterogeneity in the trade elasticities has the potential to greatly magnify the gains from trade. Closest in spirit is perhaps the contribution by Edmond et al (2012) which measures the gains from trade originating from procompetitive effects in an oligopolistic trade model.…”
Section: Introductionmentioning
confidence: 99%
“…Arkolakis et al (2012) briefly discuss a multi-industry formula in an extension but never contrast it to their aggregate formula or use it to actually calculate the gains from trade. Caliendo and Parro (2015), Hsieh and Ossa (2012), Ossa (2014), and others work with multi-industry versions of standard trade models but also do not point out that cross-industry heterogeneity in the trade elasticities has the potential to greatly magnify the gains from trade. Closest in spirit is perhaps the contribution by Edmond et al (2012) which measures the gains from trade originating from procompetitive effects in an oligopolistic trade model.…”
Section: Introductionmentioning
confidence: 99%
“…By considering the pattern of productivity growth, the estimation of Giovanni et al. is larger than that of Hsieh and Ossa (), who estimate the mean global welfare gain as 0.29%. For trade integration, Di Giovanni et al .…”
Section: Global Influencementioning
confidence: 77%
“…Studies on international trade theory have identified two channels of these spillovers: the terms‐of‐trade effect and the home‐market effect. Using data from 1995 to 2007, Hsieh and Ossa () examine the global influence of China's productivity growth through international trade and conclude that the cumulative welfare effect, through both channels, is 0.29% on average for the rest of the entire world. Di Giovanni et al .…”
Section: Global Influencementioning
confidence: 99%
“…di Giovanni and Levchenko (2010) and Levchenko and Zhang (2012), employ a more disaggregated modelling approach and emphasise differential productivity growth across industries. Their work follows the empirical tests on industry level productivity growth by Hsieh and Ossa (2011), who find small positive net gains to the rest of the world, again stemming primarily from terms of trade changes. 7 di Giovanni, Levchenko, and Zhang (2013) find small net gains for trading partners from China's growth although the distributional effects on workers emerge as large, across industry-specific skill groups.…”
Section: Global General Equilibrium Analysismentioning
confidence: 93%